THE INFLUENCE OF KNOWLEDGE SHARING BEHAVIOR ON INNOVATIVE WORK BEHAVIOR OF EMPLOYEES AT CLASS IIB YOGYAKARTA WOMEN’S CORRECTIONAL INSTITUTION - Meileni, Niken; Wibowo, Padmono (Universitas Nusa Cendana, 2025)
The existence of knowledge-sharing behavior allows the knowledge base of correctional employees to increase and gives rise to opportunities for new ideas and encourages innovative work behavior of employees. The purpose of this research is to determine the influence of knowledge-sharing behavior on the innovative work behavior of employees at the Lembaga Pemasyarakatan Perempuan Kelas IIB Yogyakarta. This research uses quantitative methods with a non-probability sampling technique of 63 employees. The data analysis techniques were processed using IBM SPSS version 25. The results of the determination test shows that the knowledge sharing behavior variable has an influence of 47.5% on the innovative work behavior variable, while the remaining 52.5% is influenced by other variables not explained in this research. From the results of this research, it can be concluded that there is a positive and significant influence between knowledge-sharing behavior and innovative work behavior in the Class IIB Yogyakarta Women’s Correctional Institution. Keywords: Knowledge Sharing Behavior; Innovative Work Behavior; Class IIB Yogyakarta Women’s Correctional Institution